THE EFFECTIVENESS OF THE LADI E-PAK KIOS IN INCREASING ACCESSIBILITY OF PUBLIC SERVICES IN KARANGREJO VILLAGE, PASURUAN REGENCY - Nabillah, Reine; Mursyidah , Lailul (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to evaluate the effectiveness of the LADI e-PAK Kiosk program in improving access to public services in Karangrejo Village, Pasuruan Regency. Method: The research employed a descriptive qualitative approach, with data collected through interviews, observations, and documentation involving village officials, kiosk operators, and residents, supported by secondary data from regulations and Ombudsman reports. The analysis was guided by Budiani’s four indicators of effectiveness: targeting accuracy, socialization, objectives, and program monitoring. Results: The findings reveal that the indicators of targeting accuracy, objectives, and program monitoring were effectively achieved, as evidenced by an increase in the number of document requests and positive community responses. However, the socialization indicator remained suboptimal due to limited direct communication from the Population and Civil Registration Office, resulting in incomplete dissemination of service information to the public. Novelty: This study contributes empirical evidence on the practical implementation of digital-based population administration services at the village level, highlighting both efficiency gains and the critical role of communication strategies in ensuring service inclusivity and sustainability.